Virus de inmunodeficiencia adquirida en paciente de 27 años con 18 semanas de gestacion - Salcedo Flores, Vanessa Del Rocio (2018)
The present clinical case was based on the study of a pregnant patient of 18 weeks, with a personal pathological history of HIV of more or less 2 years of evolution. The purpose of this case is to verify the increase in complications due to HIV in pregnant women due to the lack of information, which serves as a guide in making decisions with the pregnant woman, taking into account their incidence, and with help of the management of these patients based on the norms of the Ministry of Public Health, to analyze complications during pregnancy and the vertical transmission of HIV to the fetus. We must instruct patients and try to reduce morbidity and mortality from AIDS and associated diseases and improve the quality of life of people living with HIV, through the treatment of antiretrovirals with proven efficacy, durability and safety. According to the UN in Ecuador, they increased by 54% in 2016. From 3,152 in 2015 they increased to 4,862 last year, reports the Ministry of Public Health (MSP). On average, 13 new infections are detected every day in Ecuador, 50% of them live in Guayas (six per day)